A First Look at Usage of Free Software in Brazilian States - Lisboa, Flávio Gomes da Silva (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2023: Anais do XX Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2023.236232, 2023)
This article presents the first results of a quantitative and qualitative exploratory research in progress on the use of free software by Brazilian states. The data were colleted along the first semester of 2023. The motivation for the research was the lack of centralized and explicit data on the use of free software on the states. Initially, the free software scenario in the states is presented from the recovering of some state laws about free software. The data were collected by surveys sent to Brazilian states ombudsman under the Brazilian access to information law. All 26 brazilian states and the federal district were questioned about the use of free software, about their policies regarding software acquisition, and the development of original free software. This research contributes to knowledge about the use and production of free software by Brazilian government.